ANALYSIS OF PRICE TRANSMISSION ELASTICITY OF POTATO IN KARO DISTRICT, NORTH SUMATERA PROVINCE - Lubis, Anita Rizky; Ginting, Nelva; Panjaitan, Sandro (Sean Institute, 2023)
The price gap between the price obtained by farmers and the price obtained by retail traders indicates that the price received by retail traders is not the price received by farmers. Prices are high when production is low, on the other hand during harvest the prices obtained are usually low, even though the product may not sell well because there are many products on the market. As a result of large price fluctuations, potato is a seasonal crop and its varied production often creates uncertainty for farmers in terms of income or profits for farmers. The purpose of this research is to analyze the price transmission elasticity of potatoes in Karo Regency and to analyze the marketing margin and farmer share. This research uses secondary data for 5 years (72 months) from 2018 to 2022. The research method used to analyze price transmission elasticity is simple linear regression. The results showed that the price transmission elasticity of potatoes in Karo Regency was inelastic. The marketing margin received by potato wholesalers in Karo Regency is RP 5,348/Kg, with a percentage of 24.67%. the marketing margin received by retail potato traders in Karo Regency is RP 11,152/Kg, with a percentage of 32.11%.